Chronic treatment with a tryptophan-rich protein hydrolysate improves emotional processing, mental energy levels and reaction time in middle-aged women. Issue 2 (9th January 2015) - Mohajeri, M. H.; Wittwer, J.; Vargas, K.; Hogan, E.; Holmes, A.; Rogers, P. J.; Goralczyk, R.; Gibson, E. L.
Abstract : Common pharmacological treatments of mood disorders aim to modulate serotonergic neurotransmission and enhance serotonin levels in the brain. Brain serotonin levels are dependent on the availability of its food-derived precursor essential amino acid tryptophan (Trp). We tested the hypothesis that delivery of Trp via food may serve as an alternative treatment, and examined the effects of a Trp-rich, bioavailable dietary supplement from egg protein hydrolysate on cognitive and emotional functions, mood state, and sleep quality. In a randomised, placebo-controlled, parallel trial, fifty-nine mentally and physically healthy women aged 45–65 years received placebo ( n 30) or the supplement ( n 29) (both as 0·5 g twice per d) for 19 d. Emotional processing was significantly changed by supplementation, exhibiting a shift in bias away from negative stimuli. The results for the Affective Go/No-Go Task exhibited a slowing of responses to negative words, suggesting reduced attention to negative emotional stimuli. The results for the Facial Emotional Expression Rating Task also supported a shift away from attention to negative emotions and a bias towards happiness. An increase in arousal-like symptoms, labelled 'high energy', shorter reaction times and a slight benefit to sustained attention were observed in the treated subjects. Finally, when the supplement was taken 60–90 min before bedtime, a feeling of happiness before going to bed was consistently reported. In summary, daily consumption of a low-dose supplement containing bioavailable Trp may have beneficial effects on emotional and cognitive functions.